FAKTOR YANG MENYEBABKAN STRES KERJA DAN PENGENDALIAN STRES KERJA PADA PETUGAS PENJAGA PINTU PERLINTASAN KERETA API DI EMPLACEMENT STASIUN KODYA SEMARANG - Aulia Dewi Nuur Halimah; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Job stress is an excessive workload, feelings of distress and emotional tension which inhibit individual performance. Humans are members of more than a social group. In carrying out activities in each group, humans can encounter a stress. The same condition also occurs to a railway crossing guard in doing his task. This research used mix method approach (quantitative - qualitative). The subject of the research is the guard of the railway crossing in and around the emplacement of Semarang Kodya Station. The data were collected by spreading the questionnaire of work stress symptoms on 47 respondents and in-depth interviews at nine guards of railway crossing. Data were analyzed by using descriptive analysis on quantitative research and content analysis on qualitative research. The purpose of this study is to describe the factors that cause job stress and the monitoring of job stress of the railway crossing guard at Semarang Kodya Station. The results showed that from 47 respondents, 61.7% experienced mild stress, 21.3% did not experience work stress, and 17.0% experienced severe labor stress. The factor of job demands, work environment, career development, and external job assertion are the factors that cause job stress on the railway crossing guards at the emplacement and around the emplacement of Semarang Kodya Station (subjectively). Some ways to control the job stress of railway crossing guards who do not face with stress in controlling the saturation are playing the phone, communicating with PPKA, and trying to stay focus. If there is a problem with work or colleagues, they will deliberate with leaders and co-workers to find the best solution. To relieve fatigue during work are moving the body, cleaning and burning garbage, drinking vitamins and taking enough rest.